2016
DOI: 10.1589/jpts.28.2666
|View full text |Cite
|
Sign up to set email alerts
|

The effects of wall slide and sling slide exercises on scapular alignment and pain in subjects with scapular downward rotation

Abstract: [Purpose] The present study was performed to evaluate the changes in the scapular alignment, pressure pain threshold and pain in subjects with scapular downward rotation after 4 weeks of wall slide exercise or sling slide exercise. [Subjects and Methods] Twenty-two subjects with scapular downward rotation participated in this study. The alignment of the scapula was measured using radiographic analysis (X-ray). Pain and pressure pain threshold were assessed using visual analogue scale and digital algometer. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Some studies found that the wall slide exercise is effective to activate selectively serratus anterior . 7,15 The wall slide exercise slip upward the lower arms against the wall with elbow flexed at 90°, the shoulder joints at 90°, and the trunk fixed in a standing posture. 7 Although the wall slide exercise is not the same the posture of open chain exercise in this study, it does not have any weight bearing and focuses on the movement of a single joint, so it is similar the movement for the open chain exercise.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies found that the wall slide exercise is effective to activate selectively serratus anterior . 7,15 The wall slide exercise slip upward the lower arms against the wall with elbow flexed at 90°, the shoulder joints at 90°, and the trunk fixed in a standing posture. 7 Although the wall slide exercise is not the same the posture of open chain exercise in this study, it does not have any weight bearing and focuses on the movement of a single joint, so it is similar the movement for the open chain exercise.…”
Section: Resultsmentioning
confidence: 99%
“…Kim and Lim found that the wall side exercise might be effective in reducing pain and improving scapular alignment in subjects with scapular downward rotation rather than the sling slide exercise, such as closed chain posture. 15 Hardwick and colleagues found that a wall slide exercise activated the muscle activity of serratus anterior than other traditional exercises. 7 All the subjects in this study were healthy.…”
Section: Resultsmentioning
confidence: 99%
“…Repetitive use of UT muscle results in scapular elevation. However, during treatment of scapular muscle imbalance in a patient with SDR, it is necessary to do exercises which corrects the abnormal alignment of the scapula by strengthening the scapular upward rotators and extending the scapular downward rotators [4]. Jeong et al conducted a study on healthy adults and measured activities of UT, SA, and deltoid while performing push-up plus exercises on a stable base of support and an unstable base of support, i.e.…”
mentioning
confidence: 99%
“…a sling. He got the results that the SA and UT has higher muscle activities in a push-up plus exercise conducted on a sling [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation